Peranan Padang Lamun Selatan Bali Sebagai Pendukung Kelimpahan Ikan di Perairan Bali - Elok Faiqoh; Dwi Budi Wiyanto; I Gede Budi Astrawan (Fakultas Kelautan dan Perikanan Universitas Udayana, 2017)
Seagrass ecosystem is providing feeding ground, nursery ground, spawning ground , habitat and shelter area. The threat of physical destruction such as the reclamation, pollution, sedimentation and tourism activities decreasing the diversity and the abundance of fishery commodities. The purpose of this study was to describe the condition of seagrass, determine the composition and abundance of seagrass fish in the three Southern coast of Bali and assess the association of fish-sea grass. Samples were taken from three coastal areas, Samuh, Shindu and Serangan coastal area. The results are in Samuhthere are 6 types of seagrass, in Shindu there are 7 types and in Serangan there are three types, whichdominates with Cymodocea rotundata and Syringodium isoetifolium. From the three coastal areas,we found 21 families of fish, where the family Pomacentridaehas the highest species abundance in Samuh, Apogon sp in Serangan and Terapon sp. found in Shindu. We can see the interaction between the seagrass ecosystems of coral reefs in the waters of South Bali and ecological role of seagrass from the family and species of fish.